2018
DOI: 10.1016/j.petrol.2017.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticles on the modifications of drilling fluids properties: A review of recent advances

Abstract: Production from unconventional hydrocarbon resources, such as shale gas, shale oil, deepwater ٨ and arctic reservoirs requires advanced drilling and extraction technologies. Furthermore, ٩ minimizing the environmental footprints associated with oil recovery processes are critical. ١٠ Nanotechnology has been shown promising solutions to overcome such issues in oil and gas ١١ industry. Many studies have been conducted to analyse the enhancement of drilling fluids ١٢ through the use of nanotechnology. In these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(82 citation statements)
references
References 57 publications
0
77
0
5
Order By: Relevance
“…Nanoparticles have been proposed for wettability alteration, asphaltene deposition mitigation and removal, drilling fluid performance enhancement [7][8][9][10]. In drilling operations, they have been used for shale inhibition, fluid loss control, thermal conductivity improvement, enhancement of rheological properties [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles have been proposed for wettability alteration, asphaltene deposition mitigation and removal, drilling fluid performance enhancement [7][8][9][10]. In drilling operations, they have been used for shale inhibition, fluid loss control, thermal conductivity improvement, enhancement of rheological properties [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Płuczki zawierające w swoim składzie jeden rodzaj nanocząstek nazywane są prostymi nanopłuczkami, natomiast płuczki zawierające więcej niż jeden rodzaj nanocząstek definiowane są jako zaawansowane nanopłuczki. Literatura wskazuje, że głównymi zaletami płuczek zawierających nanomateriały są: zmniejszenie uszkodzenia złoża, korzystny wpływ na zapewnienie płynnej pracy w czasie wiercenia, skuteczność w obniżaniu filtracji płuczek wiertniczych znacznie lepsza niż stosownych do tego celu polimerów celulozowych oraz skuteczność przy likwidowaniu zaników płuczki (Abdo i Haneef, 2012;Abdo i Haneef, 2016;Zima, 2017;Rafati et al, 2018 Autorzy w swoich badaniach sprawdzili działanie nanocząsteczek boranu magnezu, boranu cynku, boranu glinu oraz boranu tytanu. Uzyskane przez autorów wyniki były bardzo korzystne.…”
Section: Nanomateriały Jako śRodki Smarneunclassified
“…Inorganic NPs, such as FeO 3 , Fe and Ca-based NPs, as well as nano-silica, can pass through the tissue of living organisms. 15 Different natural polymers (e.g., starch, 16 guar gum, 17 xanthan gum, 18 cellulose derivatives, 19 as well as synthetic polymers (e.g., polyacrylamide 20 and polyacrylates 21 ), and inorganic nanoparticles (e.g., graphene, 22 nano-silica, 23 carbon nanotubes, 23 and metal oxides 2 ) have been used as additives in DFs. All these have been applied to improve the rheological and filtration performance of DFs.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of adding NPs on the rheological and filtration properties of water-based drilling fluids has been studied by different researchers. 21,[26][27][28] The results showed that the addition of a low concentration of NPs significantly improved filtration and rheological properties. In addition, the formation of a thin and impermeable filter cake and its effectiveness depend on the NP concentration.…”
Section: Introductionmentioning
confidence: 99%